The Presidents in American history. - Beard, Charles A. (Charles Austin), 1874-1948.; Beard, William, 1907-1989. (New York, J. Messner, 1969)
Briefly summarizes the achievements of each presidential administration from Washington to Nixon. Includes a biographical digest giving basic facts about each President, a list of Vice-Presidents and cabinet members, and the results of each presidential election.
Keywords: Presidents -- United States -- Biography -- Juvenile literature; Presidents